Blood alcohol concentration effect on driving performance: A short review - Durães, N (2017)
Driving performance may be affected differently according to Blood Alcohol Concentration (BAC) levels. We conducted a short review in accordance with PRISMA statement guidelines following a search strategy which includes the combinations of on 25 search engines and 34 scientific publishers. Nine studies met inclusion criteria; the studies were analyzed regarding the type of experiment and procedures including a total of 230 participants who drove under BAC influence. Results of the studies agreed to be in the descending phase of the BAC curve that more driving errors are recorded, with loss of motor skills and cognitive impairments mainly due to the effect of acute tolerance, which affects the perception of the drivers about the risks of driving by minimizing the BAC effects. (c) 2017 Taylor & Francis Group, London.